2020
DOI: 10.1002/anie.202011632
|View full text |Cite
|
Sign up to set email alerts
|

Observing Single‐Atom Catalytic Sites During Reactions with Electrospray Ionization Mass Spectrometry

Abstract: Single‐atom catalysts (SACs) have become a prominent theme in heterogeneous catalysis, not least because of the potential fundamental insight into active sites. The desired level of understanding, however, is prohibited due to the inhomogeneity of most supported SACs and the lack of suitable tools for structure–activity correlation studies with atomic resolution. Herein, we describe the potency of electrospray ionization mass spectrometry (ESI‐MS) to study molecularly defined SACs supported on polyoxometalates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 84 publications
0
34
0
Order By: Relevance
“…Previously, we reported similar catalysts to identify active sites during hydrogenation, as well as the CO and benzyl alcohol oxidation reactions. [13][14][15][16] Herein, we find a unique interplay between positively charged Pd and a reducible Mo-based support for hydrogen spillover. Due to the solubility of the SAC in polar solvents, techniques like electrospray ionisation mass spectrometry (ESI-MS), liquid phase 1 H NMR and UV-Vis spectroscopy become viable tools for the characterisation of the process.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Previously, we reported similar catalysts to identify active sites during hydrogenation, as well as the CO and benzyl alcohol oxidation reactions. [13][14][15][16] Herein, we find a unique interplay between positively charged Pd and a reducible Mo-based support for hydrogen spillover. Due to the solubility of the SAC in polar solvents, techniques like electrospray ionisation mass spectrometry (ESI-MS), liquid phase 1 H NMR and UV-Vis spectroscopy become viable tools for the characterisation of the process.…”
Section: Introductionmentioning
confidence: 89%
“…1) while PW11O39 was synthesised following the procedure described in our previous study. 16 Mixing equimolar ratios of the lacunary POM and metal salts with weakly coordinating ligands yielded in situ the active site, PMo11O39Pd1, which can be easily and unambiguously characterised by 1a, b and Supplementary Fig. 2).…”
Section: Hydrogen Spillover On Pmo11o39pd1mentioning
confidence: 99%
See 2 more Smart Citations
“…[106] Very recently, Yan and co-workers reported that POM-SACs can be used as gas-phase models to study reaction mechanisms, e.g., for CO and alcohol oxidation. [107] The group used high-resolution electrospray ionization mass spectrometry together with DFT calculations to explore mechanisms, reaction intermediates as well as kinetic and thermodynamic properties. The study demonstrates that the use of POM-SACs as model catalysts, together with combined cutting-edge experimental and theoretical methods lead to unprecedented levels of insight into complex reaction pathways.…”
Section: Gas-phase Catalysismentioning
confidence: 99%